2015
DOI: 10.1080/13235818.2015.1053167
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and adaptive radiation in the Mytiloidea (Bivalvia): clues from the pericardial–posterior byssal retractor musculature complex

Abstract: Mytiloidea can be divided into four anatomical categories based upon the relationship between the location of the pericardium and the positions and arrangements of the posterior byssal retractor muscle units. In Category 1, the pericardium is situated above multiple posterior byssal retractor muscle blocks and is typical of the Modiolinae only. This subfamily contains among the oldest mytiloid fossils and is considered to represent the earliest condition. In Category 2, the pericardium is situated anterior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…Female L. lithophaga individuals released eggs in two parallel streams (Fig. 3c ) reflecting how the paired ovaries and gonadal apertures open into their supra-branchial chambers 14 (Fig. 4e ).…”
Section: Resultsmentioning
confidence: 99%
“…Female L. lithophaga individuals released eggs in two parallel streams (Fig. 3c ) reflecting how the paired ovaries and gonadal apertures open into their supra-branchial chambers 14 (Fig. 4e ).…”
Section: Resultsmentioning
confidence: 99%
“…The problem arises from the fact that few mytilid taxa have been described anatomically so that ascertained diagnostic differences between them mainly comprise shell features such that virtually all of the classification schemes described above are based on these characters. Only a few authors have examined mytiloid morphology and these have been identified by Morton (2015a). Notwithstanding, the most recent classifications of the Mytiloidea have arisen from the results of molecular studies.…”
Section: Introductionmentioning
confidence: 99%
“…(2000), Steiner & Hammer (2000) and Giribet & Wheeler (2002) all suggest that the Mytiloidea constitutes a monophyletic clade, which shell morphology evidence broadly supports. Distel (2000) and Steiner & Hammer (2000) suggested, however, that subfamilial relationships of the Mytiloidea need re-examination and to this end Morton (2015a) re-examined the pericardial-posterior byssal retractor muscle relationships of a large number of mytiloid taxa and concluded that the superfamily comprised four families – the Modiolidae, Mytilidae, Musculidae and Crenellidae – a view which supported the classification suggested by Bieler & Mikkelsen (2006) albeit with the latter author's addition of the Septiferidae. Finally, in a classification including fossil taxa, Carter et al (2011), recognized the extinct Modiolopsoidea P. Fischer, 1886 as separate from the Mytiloidea and suggested that the latter comprised three families and 10 subfamilies – the Mytilidae (with the Mytilinae, Arcuatulinae, Bathymodiolinae, Lithophaginae, Modiolinae and the extinct Xenomytilinae Squires and Saul, 2006), Crenellinae (with the Crenellinae and Musculinae) and Septiferidae (with the Septiferinae and Limnoperninae).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos anatômicos identificaram supostas associações entre diferentes modos de vida e possíveis adaptações morfológicas, relacionadas principalmente ao formato e estrutura das valvas, organização da musculatura adutora e presença de especializações do manto Morton, 2015). Contudo, a maioria dessas hipóteses não foi testada em um contexto filogenético ou por métodos comparativos.…”
Section: Introductionunclassified